Hollow microsphere-endowed membranes with ultrahigh-flux dye/salt separation and robust antifouling - Dengshuo Cui; Tianmeng Zhang; Rongwei Zhu; Huaqiang Feng; Xiaofeng Shen; Guijian Liu; Yanfeng Liu; Xiuyan Wang; Kai Wu; Qi Zhou; Jianfeng Zhang; Xiaoyan Yang; et al. (Desalination, 2026)

Sustainable recovery of toxic anionic surfactants for treatment of emulsified wastewater via ion-exchange electrospun membranes - Jiaru Zhang; Tianmeng Zhang; Yu He; Rongwei Zhu; Yanfeng Liu; Xiuyan Wang; Kai Wu; Qi Zhou; Jianming Yu; Han Zuilhof; Hao Lu; Jichun You (Journal of Environmental Chemical Engineering, 2026)

A subcellular spatial profiling platform for expanding the drug toxicity window - Liu Yang; Qingjie Bai; Shuyuan Guo; Luyao Hu; Chenghao Bi; Litao Shao; Zihao Lin; Kairui Cui; Shenshen Yang; Jinxia Wei; Liwei Shao; Liwen Han; et al. (Chemical Engineering Journal, 2026)

A Bayesian optimization stacked ensemble learning method: Predicting ash content in flotation cleaned coal using X-ray fluorescence oxides data - Ning Han; Yifei Li; Zhiyuan Zhang; Jiabao Gong; Bolin Zhang; Yanfeng Li (Minerals Engineering, 2026)

Multilayer thermochromic radiative cooling smart window for building thermal regulation - Hao Zeng; Liangmiao Zhang; Kailin Han; Yibo Xue; Yanfeng Gao (Energy and Buildings, 2026)

Genome analysis of Acrophialophora yunnanensis and its lignocellulolytic enzyme system - Manli Luo; Yingxia Lu; Shui Zhao; Chunbo Dong; Yanwei Zhang; Yanfeng Han (World Journal of Microbiology and Biotechnology, 2026)

A review of the environmental distribution, sources, transformation, and (eco)toxicities of tetrabromobisphenol A, its derivatives, and by-products - Yanfeng Zhang; Weihao Xu; Ya Jiao; Xiaoxuan Han; Chenshi Luo; Yong Tian (Environmental Monitoring and Assessment, 2026)

Analysis of the lignin-degrading mechanism of Acrophialophora curvata and optimization of the conditions for its straw degradation - Yingxia Lu; Hailong Zhang; Hongqin Qu; Jiarui Liu; Lan Peng; Chunbo Dong; Yanwei Zhang; Yanfeng Han (Fungal Biology, 2026)

Study on the mechanism of fat coal compatibility driven by structure transformation - Xuhui Chen; Ruyuan Duan; Ruifang Hou; Xin Jin; Bo Wu; Yanfeng Shen; Beibei Cui; Liping Chang; Chunhao Liang; Xinjie Han; Meijun Wang (Fuel, 2026)

Boundary-controlled prediction of the Sauter mean bubble diameter in three-phase fluidized bed flotation columns - Jikang Han; Changlong Zheng; Zhuang Li; Peng Chen; Yuhui Wang; Yanfeng Li (Chemical Engineering Journal, 2026)

Based on generative adversarial networks combined with gradient descent-A new method for evaluating the importance of coal oxide characteristics - Ning Han; Yifei Li; Zhiyuan Zhang; Jiabao Gong; Yanfeng Li (Fuel, 2026)

Feather-Induced Enrichment of Onygenales Triggers Cross-Kingdom Functional Shifts in Soil Fungal Communities - Chengyun Zhang; Hongqin Qu; Haiyan Wang; Yingxia Lu; Xu Li; Qingsong Ran; Chunbo Dong; Yanwei Zhang; Yanfeng Han (Current Microbiology, 2026)

Effect of different injectors on the performance of methanol direct injection engines - Gong Yanfeng; Han linghai; Zhang Lianfang; Qian Dingchao; Li Xian; Xie Fangxi (Fuel, 2026)

Synergistic carbon-doping strategy to simultaneously enhance sensing response and humidity resistance in In2O3-based NO2 sensors - Yongjie Zhang; Jingnan Jiao; Wenjiang Han; Hong Zhang; Kengo Shimanoe; Tiantian Zhou; Yanfeng Sun; Geyu Lu (Chemical Engineering Journal, 2026)

From Leaves to Roots: How Foliar IAA Application Alters Fungal Network in the Rhizosphere and Endosphere of Eucommia ulmoides - Zhaoying He; Shenglv Lu; Keyun Song; Qingsong Ran; Qiuyu Shao; Chunbo Dong; Yanwei Zhang; Yanfeng Han (Current Microbiology, 2026)

Coconut-shell biochar fixed-bed for groundwater remediation: Co-removal of microplastics and perfluorooctanoic acid - Xinle Han; Jing Xu; Yanfeng Shi; Lixingzi Wu; Ling Fu; Weina Xue; Yanhao Zhang; Xu Zhang; Xuli Jing; Zhibin Zhang (Journal of Environmental Chemical Engineering, 2025)

Temperature-driven deterministic-dominated microbial assembly underpins seasonal divergence in Baijiu high-temperature Daqu - Huabin Tu; Guanyu Zhou; Fanggen Tan; Fan Yang; Ying Han; Jianghua Li; Yanfeng Liu; Yaokang Wu; Jian Chen; Li Wang (Food Bioscience, 2025)

Reducing lateral earth pressure of expansive soils on retaining walls using EPS geofoam inclusions: Field study and estimation approaches - Weilie Zou; Qi Xiang; Qiuyang Pei; Zhong Han; Yanfeng Zhuang; Yuliang Lin; Hao Zhang; Zhiren Dai; Hongri Zhang (Computers and Geotechnics, 2025)

Bioinspired TriPhase Interfacial Design Promotes Mass Transfer for Enhanced Photocatalytic Nitrogen Fixation - Mingzhi Zhu; Lei Dong; Yiheng Wei; Bin Xue; Xiuyan Wang; Tianmeng Zhang; Yanfeng Liu; Kai Wu; Guibin Li; Han Zuilhof; Hao Lu (Chemical Engineering Journal, 2025)

Memristor-based RDBO-CNN circuit design and application of image multi-classification recognition - Gaoyong Han; Guanxiang Cheng; Yanfeng Wang; Junwei Sun (Cognitive Neurodynamics, 2025)

Waste wood in agroforestry systems improves phallus dongsun yield by regulating soil bacterial interactions and improving soil properties - Wei Ge; Yang Gui; Guosheng Zhu; Wanbing Huang; Biao Li; Hongyu Liu; Yingying Lu; Qingcheng Liu; Chunbo Dong; Yanfeng Han (Applied Soil Ecology, 2025)

The effect of enhanced rock weathering on soil respiration was modulated by understory removal in a subtropical fir plantation - Renshan Li; Yankuan Zhang; Yanfeng Bai; Xiongqing Zhang; Fangfang Zhang; Xinkuan Han; Honggang Sun; Weidong Zhang; Qingpeng Yang; Silong Wang (Agricultural and Forest Meteorology, 2025)

Chlorine-anion doping enhances the metal-oxygen covalency of Bi0.5Sr0.5FeO3-δ air electrode: achieving superior catalytic activity for reversible solid oxide cells - Hui Ye; Zhipeng Miao; Yanfeng Fu; Pengkai Shan; Bin Qian; Lin Ge; Han Chen; Yifeng Zheng; Sheng Cui (Chemical Engineering Journal, 2025)

Ag nanoparticles anchored on oxygen vacancy-rich alumina catalyst for efficient bacterial inactivation - Ting Wang; Fangyuan Gu; Leyang Xu; Wenqi Tang; Yanfeng Han; Yongjie Wang; Shi Yang; Weiying Wang; Xinlong Zhang; Tianshuo Zhao; Biao Ran; Chaopeng Fu; et al. (Chemical Engineering Journal, 2025)

Effects of physicochemical factors on transport and retention of polystyrene microplastics (PS-MPs) in homogeneous and heterogeneous saturated porous media - Lixingzi Wu; Yanfeng Shi; Ling Fu; Xinle Han; Yanhao Zhang; Xu Zhang; Weina Xue; Xuli Jing; Jing Xu; Zhibin Zhang (Environmental Geochemistry and Health, 2025)

The effect of inclined plate motion on the classification efficiency of quartz sand in the Reflux Classifier - Zhiyuan Zhang; Dongjiao Gui; Peng Chen; Yifei Li; Ning Han; Yanfeng Li (Minerals Engineering, 2025)

High- and low-quality litter are equally important to the improvement of grassland soil multifunctionality and quality - Liheng Xing; Yu Li; Jia Zeng; Jingbo Fang; Yanfeng Niu; Yang Guo; Linshan Yuan; Chengjie Ren; Gaihe Yang; Xinhui Han (Journal of Environmental Management, 2025)

Effect of hydrochemical conditions on transport of HFPO-DA in saturated quartz sand and limestone porous media - Yanfeng Shi; Xinle Han; Lixingzi Wu; Ling Fu; Weina Xue; Xuli Jing; Jing Xu; Zhibin Zhang; Botao Ding (Environmental Geochemistry and Health, 2025)

Deciphering drought adaptation in Eucommia ulmoides: From the rhizosphere microbiota to root metabolites - Xueqian Zhang; Shuangshuang Hou; Xinyu Ma; Chenglong Li; Qingsong Ran; Yanfeng Han; Chunbo Dong (Applied Soil Ecology, 2025)

Characterization of flavor profiles of wines produced with Coniella vitis-infected grapes by GC–MS, HPLC, and sensory analysis - Xing Han; Yanfeng Wei; Lifang Yuan; Xiangtian Yin; Yao Liu; Chundong Wang; Xilong Jiang; Tinggang Li; Qibao Liu (Food Chemistry, 2025)

Effects of ionic strength, cation type and pH on the cotransport of microplastics with PFOA in saturated porous media - Xu Zhang; Lixingzi Wu; Xinle Han; Yuzhi Shi; Jiwen Huang; Botao Ding; Yanhao Zhang; Zhibin Zhang; Yanfeng Shi; Fulin Li (Chemosphere, 2025)

Health impacts of PM2.5 emissions from brake pad wear: A comprehensive study on pulmonary, metabolic, and microbiota alterations - Li Zhou; Chenchen Song; Yuhan Lei; Lianlian Zhao; Yunlin Han; Yanfeng Xu; Baicun Li; Jianguo Guo (Toxicology, 2025)

Eucommia ulmoides adapts to drought stress by recruiting rhizosphere microbes to upregulate specific functions - Chunbo Dong; Yongqiang Liu; Anrui Hu; Chenglong Li; Xueqian Zhang; Qiuyu Shao; Qingsong Ran; Xu Li; Yanfeng Han (Biology and Fertility of Soils, 2025)

A portable microfluidic platform for ultra-sensitive detection of ovarian cancer biomarkers via cascade signal amplification - Yuzhen Wang; Wenxiu Long; Yanping Wang; Yuanyue Han; Fei Zeng; Jingjing Li; Bangshun He; Yujun Song; Yanfeng Gao (Chemical Engineering Journal, 2025)

Navigating Asia’s sustainable growth trajectory: a cross-regional comparative analysis - Xinjie Li; Donghyun Choi; Jeong Hugh HAN; Po-Lin Lai; Yanfeng Liu (Environmental Science and Pollution Research, 2024)

Magnetic field improvement of the germination of brown rice in the absence/presence of gibberellin: Changes in α-amylase activity and starch structural and physicochemical properties - Lu Han; Pei Wang; Yang Tao; Runqiang Yang; Yongbin Han; Yanfeng Ding; Dandan Li (Food Bioscience, 2024)

Cooperative interaction between Pediococcus and Bacillus communities as a key factor in the high-temperature Thermal differentiation of Daqu - Huabin Tu; Guanyu Zhou; Jianjun Lu; Fanggen Tan; Ying Han; Fan Yang; Hai Du; Yanfeng Liu; Jianghua Li; Li Wang; Jian Chen (Food Bioscience, 2024)

Analysis of Straw Degradation and Whole Genome of Acrophialophora multiforma - Shui Zhao; Yufeng Zhao; Keyun Song; Yanling Wang; Yingxia Lu; Chunbo Dong; Yanwei Zhang; Yanfeng Han (Current Microbiology, 2024)

Oceanic response to tropical cyclone in the northern South China Sea observed by underwater gliders during 2018 and 2020 - Yanfeng Zhang; Han Zhang; Xiaodong Tang; Shaoqiong Yang; Yanhui Wang; Xiayan Lin; Di Tian; Dake Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Aridity shapes distinct biogeographic and assembly patterns of forest soil bacterial and fungal communities at the regional scale - Xing Wang; Jia Zeng; Fang Chen; Zhengchen Wang; Hanyu Liu; Qi Zhang; Weichao Liu; Wenjie Wang; Yang Guo; Yanfeng Niu; Linshan Yuan; Chengjie Ren; et al. (Science of The Total Environment, 2024)

Evaluation of industrial performance of a new three phase fluidized bed flotation column-Based on product size characterization - Ning Han; Yifei Li; Zhiyuan Zhang; Jikang Han; Shuai Ren; Yanfeng Li (Fuel, 2024)

Evaluation of forage quality in various soybean varieties and high-yield cultivation techniques - Baiquan Sun; Shan Yuan; Mahmoud Naser; Yanfeng Zhou; Hongchang Jia; Yang Yu; Xiangyu Yao; Tingting Wu; Wenwen Song; Bingjun Jiang; Hongxia Dong; Chunlei Zhang; et al. (Field Crops Research, 2024)

Construction of artificial microbial consortia for efficient degradation of chicken feathers and optimization of degradation conditions - Wencai Xia; Mei Jin; Xin Li; Chunbo Dong; Yanfeng Han (World Journal of Microbiology and Biotechnology, 2024)

Seed endophytes reshape rhizosphere microbiota to promote the growth of Eucommia ulmoides seedlings - Qingsong Ran; Chunbo Dong; Qingqing Zhang; Qiuyu Shao; Yanwei Zhang; Xianhua Long; Yanfeng Han (Applied Soil Ecology, 2024)

Transcriptomics Reveals the Mechanism of Purpureocillium lilacinum GZAC18-2JMP in Degrading Keratin Material - Shumei Han; Yingxia Lu; Lan Peng; Xuan Dong; Liping Zhu; Yanfeng Han (Current Microbiology, 2024)

From cell membrane to endoplasmic reticulum: Tunable lipid membrane imaging by regulating the lipophilicity and internalization of carbon dots - Yanzhi Xing; Jiaxin Li; Han Leng; Yanfeng Zhang; Shuang E; Jianhua Wang; Xuwei Chen (Chemical Engineering Journal, 2024)

Decoding the aroma characteristics of icewine by partial least-squares regression, aroma reconstitution, and omission studies - Xu Qian; Mengqi Ling; Yanfeng Sun; Fuliang Han; Ying Shi; Changqing Duan; Yibin Lan (Food Chemistry, 2024)

Interactions of rhizosphere microbiota–environmental factors–pharmacological active ingredients of Eucommia ulmoides - Chunbo Dong; Qiuyu Shao; Qingsong Ran; Xu Li; Yanfeng Han (Planta, 2024)

Accumulated CO2 affects growth, acid-base regulation and ion balance of turbot (Scophthalmus maximus) in a recirculating aquaculture system - Teng Guo; Yanfeng Wang; Jiyuan Li; Xiaoyang Guo; Shihong Xu; Houwei Han; Jiachen Yu; Jun Li; Qinghua Liu (Aquaculture, 2024)

Study on the dynamic effects of plateau hypoxic and cold environment on the thermal adaptation of short-term sojourners in Xizang - Guannan Duan; Cong Song; Yanfeng Liu; Zhiguo Fu; Cong Zhang; Xu Han; Yong Li; Yong Zhou (Journal of Thermal Biology, 2024)

Engineered Saccharomyces cerevisiae for de novo δ-tocotrienol biosynthesis - Luyao Han; Yaokang Wu; Yameng Xu; Chenyang Zhang; Yanfeng Liu; Jianghua Li; Guocheng Du; Xueqin Lv; Long Liu (Systems Microbiology and Biomanufacturing, 2024)

Community diversity and co-occurrence patterns of keratinophilic microorganisms in hospital garden soils - Yulian Ren; Zhiyuan Zhang; Chunbo Dong; Wei Ge; Zongqi Liang; Yanfeng Han (Pedobiologia, 2023)

Static magnetic field improvement of the quality of rice dumpling subjected to freeze–thaw cycles: Roles of phase transition of water and changes in structural and physicochemical properties of glutinous rice flour - Dandan Li; Haifei Li; Yang Tao; Ganghua Li; Enbo Xu; Yongbin Han; Yanfeng Ding (Food Research International, 2023)

A newly isolated Bacillus megaterium OQ560352 promotes maize growth in saline soils by altering rhizosphere microbial communities and organic phosphorus utilization - Qili Zhu; Jiachao Zhou; Min Sun; Hongshun Li; Yejun Han; Jimin Lv; Yanfeng Li; Xixing Zhang; Timothy S. George; Wei Liu; Zihao Wang; Yingxiang Sun (Rhizosphere, 2023)

The Analysis of Microbial Community Characteristics Revealed that the Pathogens of Leaf Spot of Rosa roxburghii Originated from the Phyllosphere - Yuxing Liu; Wei Ge; Chunbo Dong; Qiuyu Shao; Zhiyuan Zhang; Xiao Zou; Haiyan Hu; Yanfeng Han (Indian Journal of Microbiology, 2023)

Assembly Processes and Biogeographical Characteristics of Soil Bacterial Sub-communities of Different Habitats in Urban Green Spaces - Yulian Ren; Qiuyu Shao; Wei Ge; Xin Li; Haiyan Wang; Chunbo Dong; Yanwei Zhang; Sunil Kumar Deshmukh; Yanfeng Han (Current Microbiology, 2023)

Specialist species of fungi and bacteria are more important than the intermediate and generalist species in near-urban agricultural soils - Yulian Ren; Wei Ge; Chunbo Dong; Haiyan Wang; Shui Zhao; Chenglong Li; Jinhui Xu; Zongqi Liang; Yanfeng Han (Applied Soil Ecology, 2023)

Preparation of germinated brown rice with high γ-aminobutyric acid content and short root by magnetic field treatment - Caiwen Chen; Yang Tao; Yongbin Han; Yanfeng Ding; Xingliang Jian; Dandan Li (Journal of Cereal Science, 2023)

Ecological carrying capacity and carbon sequestration potential of bivalve shellfish in marine ranching: A case study in Bohai Bay, China - Zepeng Li; Yan Chen; Gang Wang; Jiandong Mu; Yanfeng Sun; Haolin Yu; Jiangling Xu; Ying Yan; Shuangyue Luo; Fuqiang Han; Jie Feng; Zhe Pan (Frontiers in Marine Science, 2023)
Introduction Shellfish play an important role in ecological restoration and as carbon (C) sinks, but studies on their ecological carrying capacity (ECC) and C sequestration potential are sparse. Methods In this study, we selected a 57-hectare artificial oyster reef in a typical marine ranching in Bohai Bay, China, to evaluate the ECC and their C sequestration potential of bivalve shellfish, and projecting their impact on functional groups in the system, with an Ecopath with Ecosim (EwE) food web model. We conducted four biological surveys to obtain the biomass measurements, with one conducted in each of the summer, autumn, and winter of 2019 and one in the spring of 2020; and the functional groups included in the surveys comprised fish, cephalopods, crustaceans, snails, bivalve shellfish, annelids, other macrobenthos, meiobenthos, starfish, sea cucumbers, zooplankton, phytoplankton, and detritus. Results and Discussion The EwE model prediction results showed that the ECC of bivalve shellfish was established to be 282.66 t/km 2 , far more than the existing quantity of 187.76 t/km 2 . Therefore, at present, the ecosystem of the study marine ranching is not yet mature. Moreover, our ecological network analysis parameters indicated that the marine ranching ecosystem will be mature and stable when the bivalve shellfish population reaches its ECC. However, the increase in bivalve shellfish biomass will result in a decrease in the population sizes of species competing for food resources with bivalve shellfish, mainly gobiid fish such as Tridentiger bifasciatus, Tridentiger trigonocephalus, Tridentiger barbatus . Simultaneously, when the bivalve shellfish reach their ECC, 29.23 t of CO 2 can be sequestrated by bivalve shellfish, comprising 14.32 t being removed from the ecosystem as prey and 14.91 t being stored on the seafloor through biodeposition. Conclusion Therefore, the research demonstrated that, within the scope of ECC, the increasing bivalve shellfish can improve the C sequestration capacity of the marine ranch ecosystem, and effective management of bivalve shellfish in marine ranching can improve the economic benefits and C sink service functions of marine ranching.

UNC93B1 facilitates TLR18-mediated NF-κB signal activation in Schizothorax prenanti - Shiyong Yang; Weikai Sui; Xiaoyu Ren; Xiaoyu Wang; Guixian Bu; Fengyan Meng; Xiaohan Cao; Guozhi Yu; Xingfa Han; Anqi Huang; Qiuxia Liang; Jiayun Wu; et al. (Fish & Shellfish Immunology, 2023)

Effects of Medicinal Plants on Fungal Community Structure and Function in Hospital Grassplot Soil - Qiuyu Shao; Chunbo Dong; Haiyan Hu; Jianzhong Huang; Xiao Zou; Zongqi Liang; Yanfeng Han (Current Microbiology, 2022)

Screening and identification of HLA-A2-restricted neoepitopes for immunotherapy of non-microsatellite instability-high colorectal cancer - Ranran Shi; Yubing Li; Ling Ran; Yu Dong; Xiuman Zhou; Jingwen Tang; Lu Han; Mingshuang Wang; Liwei Pang; Yuanming Qi; Yahong Wu; Yanfeng Gao (Science China Life Sciences, 2022)

Structure and Function of Bacterial Microbiota in Eucommia ulmoides Bark - Chunbo Dong; Ting Yao; Zhiyuan Zhang; Wanhao Chen; Jiangdong Liang; Yanfeng Han; Jianzhong Huang; Sunil K. Deshmukh; Zongqi Liang (Current Microbiology, 2020)

Biophotonic Activity and Transmission Mediated by Mutual Actions of Neurotransmitters are Involved in the Origin and Altered States of Consciousness - Weitai Chai; Zhengrong Han; Zhuo Wang; Zehua Li; Fangyan Xiao; Yan Sun; Yanfeng Dai; Rendong Tang; Jiapei Dai (Neuroscience Bulletin, 2018)

Employing response surface methodology (RSM) to improve methane production from cotton stalk - Han Zhang; Habiba Khalid; Wanwu Li; Yanfeng He; Guangqing Liu; Chang Chen (Environmental Science and Pollution Research, 2018)

AnkG hemizygous mice present cognitive impairment and elevated anxiety/depressive-like traits associated with decreased expression of GABA receptors and postsynaptic density protein - Cui Liu; Ling Zhang; Jie Wu; Xiaolong Sui; Yanfeng Xu; Lan Huang; Yunlin Han; Hua Zhu; Yanhong Li; Xiuping Sun; Chuan Qin (Experimental Brain Research, 2017)

Generation of mutant threonine dehydratase and its effects on isoleucine synthesis in Corynebacterium glutamicum - Yanfeng Guo; Jianzhong Xu; Mei Han; Weiguo Zhang (World Journal of Microbiology and Biotechnology, 2015)

Nitric oxide mediates hypocrellin accumulation induced by fungal elicitor in submerged cultures of Shiraia bambusicola - Wen Du; Jiandong Liang; Yanfeng Han; Jianping Yu; Zongqi Liang (Biotechnology Letters, 2015)

Application of Physiologically Based Absorption Modeling to Formulation Development of a Low Solubility, Low Permeability Weak Base: Mechanistic Investigation of Food Effect - Hefei Zhang; Binfeng Xia; Jennifer Sheng; Tycho Heimbach; Tsu-Han Lin; Handan He; Yanfeng Wang; Steven Novick; Ann Comfort (AAPS PharmSciTech, 2014)

Effects of microbial elicitor on production of hypocrellin by Shiraia bambusicola - Wen Du; Zongqi Liang; Xiao Zou; Yanfeng Han; Jiandong Liang; Jianping Yu; Wanhao Chen; Yurong Wang; Chunlong Sun (Folia Microbiologica, 2013)

Antibacterial activity of hypocrellin A against Staphylococcus aureus - Wen Du; Chunlong Sun; Zongqi Liang; Yanfeng Han; Jianping Yu (World Journal of Microbiology and Biotechnology, 2012)

In vitro assessment of immunomodulating activity of the two Lactobacillus strains isolated from traditional fermented milk - Yanfeng Tuo; Lanwei Zhang; Xue Han; Ming Du; Yingchun Zhang; Huaxi Yi; Weiqin Zhang; Yuehua Jiao (World Journal of Microbiology and Biotechnology, 2011)